VD_FINDINFO HC / 2016 / 499 vom 9. Mai 2016 - VD Tribunal cantonal (2016)
OBLIGATION D'ENTRETIEN, ENFANT, REVENU HYPOTHÉTIQUE, DIRECTIVEINJONCTION, DÉBITEUR | 276 al. 2 CC, 285 CC, 48 LDIP, 65 al. 1 LDIP